Postoperative patient handovers—Variability in perceptions of quality: A qualitative focus group study. Issue 3 (24th September 2018) - Reine, Elizabeth; Rustøen, Tone; Ræder, Johan; Aase, Karina
Abstract: Aims and objectives: (a) To explore the factors affecting quality in postoperative handovers as perceived by the different professional groups of clinicians involved. (b) To explore possible differences in perceptions of postoperative handover quality across professional groups and level of experience. Background: High quality patient handovers after surgery and anaesthesia are important to ensure patient safety. There is a paucity of research describing contextual factors related to handover quality and the perspectives of different professional groups involved. Design: A qualitative exploratory design was applied. Method: A total of eight focus group interviews with 37 participants (29 nurses, eight doctors) were conducted. Anaesthesiologists, resident anaesthesiologists, nurse anaesthetists, postoperative care nurses and operating room nurses participated in the study. The interviews were conducted according to profession with two groups per profession: one with experienced clinicians and one with less experienced clinicians. The data were analysed using thematic analysis. The study adheres to the COREQ guidelines. Results: The data analysis identified the following factors affecting postoperative handover quality: "timing and concurrency conflicts, " "handover structure, " "patient conditions, " "individual characteristics of clinicians involved" and "team composition." Differences across professional groups and level of experience were related to responsibility, structure and adaptation. Conclusion: The professional groups involved describe the postoperative patient handover as a complex and variable process that needs to be carefully planned and executed according to the influencing factors. Variability exists across professional groups and level of experience. Relevance to clinical practice: Health care providers need to be aware that postoperative handovers are affected by a set of factors related to internal (patient conditions, individual characteristics of clinicians involved and team composition) and external (timing and concurrency conflicts, handover structure) characteristics. These issues need to be acknowledged when procedures and routines for handover quality are designed, implemented and used.